Correlates of successful home-based garment entrepreneurs in the province of Rizal - Ramos, Digna Castro (2001)
This study was designed to determine the correlates of successful home-based garment entrepreneurs in the province of Rizal. The respondents comprised of 67 registered and 45 unregistered garment entrepreneurs for a total of 112 entrepreneurs who were purposively chosen in the four selected municipalities in Rizal province. In-depth personal interviews and direct observation were combined to gather data using structured questionnaire. Case studies were also used to strengthen the findings. Gender, monthly family income, previous training/experiences and years in business were found to be significant correlates of success at .01 level and educational attainment at .05 level. Facilities and sources of capital were found to be highly significant correlates of success in the garment entrepreneurship. Material resources were expressed in terms of economic progress, benefits given and expansion in business while the non-material resources were manifested in community involvement, home and working environment. Among exporters, dominant character traits found were "information seeking", "risk taking" and "opportunity seeking". There were no significant differences among local, export and local export, between sole proprietorship and partnership and between registered and unregistered garment entrepreneurs in terms of environmental factors.